Integrating Play Therapy into Early Childhood Education Management: An Inclusive Strategy for Psychosocial Intervention in School Settings - Alice Erni Husein; Mariska Putri Pratiwi; Zakarias Situmorang (Dinasti Publisher, 2025)
This study explores the strategic integration of play therapy within early childhood education management as a means to promote inclusive education and holistic child development. Drawing on a qualitative secondary data analysis of policy documents, academic literature, and theoretical models, the research identifies key frameworks, challenges, and sustainable strategies for embedding therapeutic interventions in school systems. Findings suggest that play therapy contributes significantly to emotional regulation, social inclusion, trauma recovery, and individualized learning—core components of equitable education. However, the institutionalization of play therapy faces various barriers, including policy gaps, resource limitations, staff training deficits, and cultural stigma surrounding mental health. The paper concludes with a set of actionable recommendations for educational leaders and policymakers to build systemic readiness and long-term sustainability through cross-sectoral collaboration, curriculum alignment, and inclusive leadership practices.